ANALISIS PEMIKIRAN MUHAMMAD SYUHUDI ISMAIL DALAM MEMAHAMI HADIS - Taufan Anggoro (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
Muhammad Syuhudi Ismail in understanding the hadith took several steps: First, conducting text analysis; Second, to identify the historical context for the appearance of hadith; and Third, to contextualize hadith. Through these three steps, the structure of the thought of Muhammad Syuhudi Ismail in understanding hadith is so strong especially in analyzing text-context. Therefore, it is appropriate if the thought of Muhammad Syuhudi Ismail actually revealed the existence of modern forms of hermeneutic surgery. This is a result of the intense activity of Muhammad Syuhudi Ismail in various existing discourses so that his thoughts in the study of hadith were influenced by intellectual figures and hadith scholars such as Fazlurrahman, Imam al-Qarafi, and Shah Waliyyullah ad-Dahlawi.